Myths of Age and Sexual Maturity: Defining Girlhood in India: A Transnational History of Sexuality Maturity Laws. Issue 2 (1st June 2021) - Unknown
Abstract : Ashwini Tambe. 2019. Defining Girlhood in India: A Transnational History of Sexuality Maturity Laws. Urbana: University of Illinois Press.